Peningkatan Kemampuan Guru dalam Pembuatan RPP Bermuatan Higher Order Thinking Skill (HOTS) melalui Supervisi Akademik di SD Negeri 118275 Sialang Pamoran II Tahun Pelajaran 2019/2020 - suprapti suprapti (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2021)
The background of this school action research at SD Negeri 118274 Sialang Pamoran II is because not all teachers have lesson plans that contain HOTS. This is known based on the author's academic supervision. Therefore, the author does not want to find fault with the teachers, but to carry out one of the managerial duties as the principal. The purpose of this school action research is to determine the Improvement of Teacher Ability in Making RPP with HOTS through Academic Supervision at SD Negeri 118274 Sialang Pamoran II Academic Year 2019/2020. The method used in this research is descriptive method, using percentage techniques to see the increase that occurs from cycle to cycle. Making RPP with HOTS content, can improve the ability of teachers through academic supervision. This can be seen in the initial conditions that no one teacher was able to make RPP that contained HOTS, after academic supervision was carried out in cycle one, there were 7 teachers who were able to make HOTS lesson plans (70%) in the good category. After the academic supervision was carried out, there was an increase where as many as 10 teachers (100%) were able to make lesson plans containing HOTS with very good categories.